2015
DOI: 10.1109/jphotov.2014.2377516
|View full text |Cite
|
Sign up to set email alerts
|

Cu(In,Ga)Se$_{\bf 2}$ Thin-Film Solar Cells and Modules—A Boost in Efficiency Due to Potassium

Abstract: Thin-film solar cells based on the chalcopyrite Cu(In,Ga)Se 2 (CIGS) absorber material show high potential for further cost reduction in photovoltaics. Compared with polycrystalline silicon (p-Si) wafer technology, thin-film technology has inherent advantages due to lower energy and material consumption during production but has typically shown lower conversion efficiency. However, in the past two years, new scientific insights have enabled the processing of CIGS solar cells with efficiencies up to 21%, surpas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 40 publications
3
61
1
Order By: Relevance
“…In order to verify that approach simulations are carried out using Sentaurus TCAD (see Section 6 for more details). The band diagram of the simulated structure is Among the thin-film solar cell technologies, Cu(In,Ga)Se 2 -based solar cells demonstrate the highest efficiencies, where the recent boost in efficiency is triggered by a KF postdeposition treatment (PDT). In this contribution, Cu(In,Ga)Se 2 -based solar cells are fabricated using RbF PDTs after absorber layer growth with varying substrate and RbF source temperature.…”
Section: Quantification Of An Injection Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…In order to verify that approach simulations are carried out using Sentaurus TCAD (see Section 6 for more details). The band diagram of the simulated structure is Among the thin-film solar cell technologies, Cu(In,Ga)Se 2 -based solar cells demonstrate the highest efficiencies, where the recent boost in efficiency is triggered by a KF postdeposition treatment (PDT). In this contribution, Cu(In,Ga)Se 2 -based solar cells are fabricated using RbF PDTs after absorber layer growth with varying substrate and RbF source temperature.…”
Section: Quantification Of An Injection Barriermentioning
confidence: 99%
“…[1] A strong boost in efficiency was enabled due to the addition of a KF postdeposition treatment (PDT). [2] Recently, the addition of Rb and Cs has proven to be beneficial for device performance as well, and a 22.6% efficient CIGS device has been demonstrated using a RbF PDT. [3] The impact of the KF PDT has been investigated by several groups and mainly a modification of the CIGS surface was observed.…”
Section: Introductionmentioning
confidence: 99%
“…It has opened the experimental potential for higher CIGS solar cell efficiencies [9][10][11][12][13][14][15][16][17][18][19][20]. The EMPA group reported that KF-PDT reduces the Cu and Ga concentration at near-surface region of CIGS layer deposited onto alkali-free polyimide substrates, which leads to significant increase in the open circuit voltage (V oc ).…”
Section: Introductionmentioning
confidence: 99%
“…They interpreted the cause for increased V oc as a formation of a very dense shallow donor-type Cd Cu during the chemical bath deposition (CBD)-CdS process [9,12]. In addition, KF-PDT enables a significant reduction in the thickness of the CdS buffer layer without the commonly observed losses in device parameters [9][10][11][12][13][14][15]. Due to the Cu-deficient compounds at the very-near-surface region, a shift of the valence band to lower binding energies has been observed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcopyrite p-type Cubased metal selenides (CuInSe 2 , CuGaSe 2 , and their solid solutions) are interesting photo-absorbers for solar-energy-related applications because of their suitable direct band gap, good absorption coefficient, and high flexibility for tuning the energy band gap without relying on toxic elements [19]. It has been reported that laboratory-scale thin-film solar cells with p-Cu(In,Ga)Se 2 (CIGS) and CdS heterogeneous junctions prepared using the thermal evaporation method can attain a high conversion efficiency of 21% [20]. Kumagai et al [21] reported PEC water splitting using p-type copper gallium selenide (CGS) films deposited onto Mo-and Ticoated glass substrates using the powder transfer method.…”
Section: Introductionmentioning
confidence: 99%